ANALISIS PEMASARAN KOPI ARABIKA GAYO DI KABUPATEN ACEH TENGAH PROVINSI ACEH - Noratun Juliaviani; Sahara Sahara; Ratna winandi (Jurnal Agrisep, 2021)
This study aims to determine the general description of Gayo Arabica coffee marketing channels from farmers to consumers and to analyze the marketing efficiency of Gayo Arabica coffee in Aceh Tengah Regency. Respondents in this study were Gayo Arabica coffee farmers with a total of 40 farmers and 5 traders. Data analysis in this study uses marketing channel analysis by identifying marketing institutions involved in product distribution from the producer or farmer level to consumers and to determine the performance of Gayo Arabica coffee using quantitative analysis with marketing margins and farmer's share. The results show that in Aceh Tengah Regency there are 3 kinds of marketing channels carried out by farmers, namely: channel 1 (Farmers - Collector traders - Exporters (private) - Importers), channel 2 (Farmers - Collector traders - Cooperatives (exporters) - Importers), channel 3 (Farmers - Collectors - Cooperatives (non-exporters) - Importers). The results of the analysis of the market performance of Gayo Arabica coffee show that marketing channel 2 is the marketing channel with the lowest marketing margin, the smallest marketing cost, and the largest farmer's share compared to other marketing channels.